Relationship between Milker’s Personal Hygiene and Sanitation with Contamination of Escherichia coli in The Fresh Cow Milk in People's Livestock in Umbulharjo, Cangkringan, Sleman - Habib Azis Putra Perwira; Dyah Suryani; Wibowo Wibowo (Alliance oh Health Activists (AloHA), 2019)
Background: Fresh cow’s milk is an almost complete source of nutrition. The condition with a less clean environment can ease the occurrence of milk’s contamination. The contamination can come from a variety of sources such as cow’s skin, the udder water, soil, dust, human handling, equipment, and air. The most common contamination in cow’s milk is from bacteria. One of the bacteria is Escherichia coli. The objectives of the research are to determine the relation of the personal hygiene of the cow milkers and sanitation with Escherichia coli bacterial contamination in fresh cow’s milk. Methods: This research was a quantitative research with the cross-sectional approach with total sampling technique used which means the sample was all of the cow milkers in the village. The research used questionnaires, laboratory tests, and analysis of data used univariate and bivariate test with Fisher's exact statistical test. The laboratory tests used MPN Escherichia coli. Results: According to this research showed about 55% of respondent did not have good personal hygiene. The sanitation variable showed the majority of cow milkers did have no good sanitation about 62.5%. From 40 samples of fresh cows milk, 32 samples of milk were contaminated by the Escherichia coli. The relation between the personal hygiene of cow milkers with the contamination of Escherichia coli showed the (p-value 0.014) and for the relations between sanitation with the contamination of Escherichia coli in fresh cows milk bout (p-value 0.036). Conclusion: There was a relation between the personal hygiene of cow milkers and sanitation with Escherichia coli bacterial contamination in fresh cows milk in the people's farm of Gondang Umbulharjo, Cangkringan, Sleman. Keywords: Cow milkers, Personal hygiene, Sanitary, Escherichia coli